THE ROLE OF ARTIFICIAL INTELLIGENCE IN MODERN MEDICINE - Jumaev Fatillo Erkinbek ogli (Modern American Journals, 2025)
Artificial Intelligence (AI) is rapidly transforming modern medicine by enhancing diagnostics, treatment planning, and patient care. Through machine learning and data analysis, AI systems can detect diseases, interpret medical images, support clinical decisions, and even assist in robotic surgeries. These technologies offer faster, more accurate, and cost-effective healthcare solutions. However, the rise of AI also presents ethical, legal, and practical challenges, including data privacy concerns and algorithmic bias. This paper explores the current applications, benefits, limitations, and future potential of AI in medicine. By integrating AI responsibly, healthcare systems can improve outcomes, increase access, and support medical professionals in delivering personalized and efficient care.
Keywords: Artificial Intelligence (AI); Machine Learning; Deep Learning; Medical Diagnostics; Healthcare Technology; AI in Surgery; Predictive Analytics; Virtual Health Assistants; Personalized Medicine; Medical Data Analysis.